Book Review: "Subversion, Conversion, Development" by James Leach and Lee Wilson - Matthew Kelly (tripleC: Communication, Capitalism & Critique)
This is a review of James Leach and Lee Wilson's collected volume "Subversion, Conversion, Development: Cross-cultural Knowledge Exchange and the Politics of Design"